Eve On top : Women'S Experience Of Success In The Public Sector. - Baker, David P.; Casey, Bernadette; ScienceDirect eBooks (Burlington : Elsevier Science, 2010)
Eve on Top takes an in-depth look at the position of women in senior positions in the public sector using a case-study approach, based on ten 'successful' women and their background, upbringing, career progression, successes and failures, challenges and experiences. Each case study includes a 'lessons learned' response in the form of advice both to other women, and the organisations in which they work. Surrounding and supporting the case studies are short essays charting the main themes that emerge from the interview process, backed up by extensive literature reviews. The book also compares re.
Evidence for a 'glass ceiling'No personal experience; Not deserving of promotion?; Continued unequal treatment; The next generation; Conclusion; Chapter 10: Sacrifices, gains, balances and choices; Introduction; Sacrifices; Gains; Choices; Conclusion; Chapter 11: Domestic considerations; Introduction; Women as carers; Improved conditions; Tempted to stay at home; Being there -- or not; Supportive partners; Conclusion; Chapter 12: Working harder?; Introduction; All in the mind; Definitely not; Working harder professionally and personally; Being driven; Being modest; Working smarter.
No difference at the top.
Print version record.
Elsevier
Keywords: Women in public life -- Great Britain; Women government executives; Leadership in women; POLITICAL SCIENCE -- Government -- Executive Branch; POLITICAL SCIENCE -- Public Affairs & Administration; Leadership in women; Women government executives; Women in public life; Great Britain; Electronic books